Answer:
Option 3 - f(x)= 4x,
![g(x) = (1)/(4)x](https://img.qammunity.org/2020/formulas/mathematics/high-school/ju97svad223o3yqlwc2tf6n2bxatxguncr.png)
Explanation:
To find : Which two functions are inverses of each other?
Solution :
Two functions are inverse if
![f(g(x))=x=g(f(x))](https://img.qammunity.org/2020/formulas/mathematics/college/4v7f3to2jnn0oa3pfomo83vwnud948cjfw.png)
Now, we find one by one
1) f(x)= x, g(x) = -x
![f(g(x))=f(-x)=-x\\eq x](https://img.qammunity.org/2020/formulas/mathematics/high-school/e704jerpbicn31nlkf7qjrhm5edx9stpri.png)
Not true.
2) f(x)= 2x,
![g(x) = -(1)/(2)x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8hv45xo7cdowm6tfomhyh1k8w1wwl6iyov.png)
![f(g(x))=f(-(1)/(2)x)=2*(-(1)/(2)x)=-x\\eq x](https://img.qammunity.org/2020/formulas/mathematics/high-school/2wfsv71h8ag6xmuhiq6rptohuf7ps61q7r.png)
Not true.
3) f(x)= 4x,
![g(x) = (1)/(4)x](https://img.qammunity.org/2020/formulas/mathematics/high-school/ju97svad223o3yqlwc2tf6n2bxatxguncr.png)
![f(g(x))=f((1)/(4)x)=4*((1)/(4)x)=x](https://img.qammunity.org/2020/formulas/mathematics/high-school/3ti1uydeq45dzqa4ij0ioy36hl6pjwwxpa.png)
![g(f(x))=f(4x)=(1)/(4)* 4x=x](https://img.qammunity.org/2020/formulas/mathematics/high-school/i9tv7k7qvqmyip5ydlk8ww4w6z391wctgt.png)
i.e.
is true.
So, These two functions are inverse of each other.
4) f(x)= -8x,
![g(x) =8x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xhz1jxd8tdjvsbce3gfjz4f9gqr8wr22wo.png)
![f(g(x))=f(8x)=8*(-8x)=-64x\\eq x](https://img.qammunity.org/2020/formulas/mathematics/high-school/yu0l342iaad5w4eepoicdpd6em1gbrd1wd.png)
Not true.
Therefore, Option 3 is correct.